KORELASI TINGKAT ASUPAN LEMAK DAN AKTIVITAS FISIK DENGAN KUALITAS HIDUP LANJUT USIA Correlation between Fat Intake and Physical Activity with Quality of Life in Elderly - Roni Nurdianto; Diffah Hanim; Eti Poncorini Pamungkasari (Media Gizi Indonesia, 2021)
The quality of life of the elderly is determined by physical, emotional, intellectual, social, vocational, and spiritual. The importance of maintaining quality of life is always implemented by healthy living behaviors, eating safe and nutritious food balanced with physical activity to minimize the risk of degenerative diseases. Non-communicable diseases such as hypertension and diabetes mellitus often occur in the elderly. This is caused by so often eating high-fat foods, and lack of physical activity, which can decrease the quality of life in elderly. This study aims to analyze correlation between the level of fat intake and physical activity with quality of life of elderly. Method used was a cross sectional design with 200 respondents. Data on fat intake was obtained by interview using 2x24 hour food recall questionnaire, while physical activity and Quality of Life used the Social Disengagement Index and WHOQOL-BREF questionnaires. Data were analyzed using Spearman test (α = 0.05). This study shows that majority of respondents have a good quality of life at a moderate level of fat deficit intake and moderate activity. Results of statistical analysis, level of fat intake with quality of elderly life has a non-significant positive correlation (p> 0.05) with value of correlation is 0.086 or very weak, whereas physical activity has a significant positive correlation with quality of elderly life (p <0.05) with value of correlation is 0.216 or weak. This study concluded that it is important to keep doing physical activities to maintain physical fitness in elderly life.